Characterization and evolutionary insights into complete mitochondrial genome of Sedum sarmentosum within the family Crassulaceae - Qin, Meiling; Lü, Peng; Tang, Min; Yu, Shaoshuai; Gong, Xun (Frontiers in Plant Science, 2026)
Sedum sarmentosum Bunge is a perennial succulent plant of medicinal significance within the Crassulaceae family. To investigate its mitochondrial genome (mitogenome), structure, gene composition, and evolutionary implications, we assembled the complete mitogenome and plastid genome (ptgenome) of S. sarmentosum using high-fidelity sequencing data. The resulting mitogenome is a circular DNA molecule of 156,727 bp with a GC content of 45.30%, encoding 30 protein-coding genes (PCGs), eight tRNAs, and two rRNAs. Analyses identified 78 simple sequence repeats, two tandem repeats, and 30 dispersed repeats. A total of 617 potential RNA-editing sites were predicted, predominantly occurring at the second codon positions of mitochondrial PCGs. In addition, 18 mitochondrial plastid DNA transfer events were identified between the mitochondrial and chloroplast genomes, which included both tRNA and partial protein-coding gene segments. Moreover, the regional boundaries of chloroplasts of S. sarmentosum was identified, consisting of a large single-copy (LSC) region (81,798 bp), a small single-copy (SSC) region (16,671 bp), and two inverted repeat (IR) regions (25,778 bp each). Phylogenetic analyses based on mitogenomes of 26 species revealed that S. sarmentosum is closely related to members of the Rhodiola genus within Crassulaceae, providing new insights into evolutionary relationships among Saxifragales. Furthermore, codon usage bias, selection pressure analysis, and nucleotide diversity assessments uncovered lineage-specific patterns of molecular evolution, highlighting the balance between purifying and positive selection in shaping mitochondrial gene divergence. Altogether, this study contributes to our understanding of mitogenomic architecture, evolutionary adaptation, and phylogenetic placement of S. sarmentosum, and offers a valuable genomic resource for future studies in plant evolution, functional genomics, and molecular breeding.